Prepreg, and metal-clad laminate and wiring board using the same

CN123022734APending Publication Date: 2026-10-30PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580023837.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]然而,专利文献1及2中虽然如上所述地记载了关于树脂组合物的成分使用特定成分,但对于在使用树脂组合物制作布线板等时所使用的玻璃布,只是记载了可以使用一般的T玻璃、S玻璃等玻璃布

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022734A_ABST
    Figure CN123022734A_ABST
Patent Text Reader

Abstract

One aspect of the present application relates to a prepreg comprising: a thermosetting resin composition or a semi-cured product of the thermosetting resin composition; and a glass cloth, wherein the thermosetting resin composition contains molybdenum compound particles (A) and a maleimide compound (B), and the glass cloth contains, relative to the total amount of components of the glass cloth: 45 to 55 mass% of SiO2; 20 to 30 mass% of Al2O3; 3.0 mass% or less of MgO; and 10 to 15 mass% of P2O5.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to prepregs, and foil-coated laminates and wiring boards using the prepregs. Background Technology

[0002] With the increasing performance of electronic devices and the significant improvement in information and communication speeds in recent years, semiconductor packaging substrates used in network equipment, servers, and AI processors have also seen advancements in performance and integration, leading to thinner and larger substrates. Correspondingly, the requirements for high-performance processing capabilities, such as drilling performance, of semiconductor packaging substrates are constantly increasing.

[0003] For example, Patent Document 1 describes a resin composition containing a cyanate ester compound, an epoxy resin, a molybdenum compound, and two inorganic fillers, and describes how adjusting the ratio of the average particle size of the two inorganic fillers can improve the machinability (hole position accuracy) of mechanical drilling.

[0004] Furthermore, with the trend towards thinner and larger wiring boards, problems arise, such as the tendency for semiconductor packages with semiconductor chips mounted on the wiring board to warp, leading to poor mounting. To suppress warping of semiconductor packages with semiconductor chips mounted on the wiring board, the substrate material constituting the insulating layer of the wiring board must also possess excellent thermal expansion properties in its cured form.

[0005] For example, Patent Document 2 describes a resin composition containing molybdate compound, epoxy resin, curing agent and inorganic filler, and describes a laminate that not only has excellent mechanical drilling processability (hole position accuracy) but also has low thermal expansion.

[0006] However, while Patent Documents 1 and 2 describe the use of specific components in the resin composition as mentioned above, they only specify that ordinary T-glass, S-glass, or other similar glass cloths can be used when manufacturing wiring boards using the resin composition. Therefore, there is still room for further improvement in suppressing warping of semiconductor packages on which semiconductor chips are mounted on wiring boards and in improving drilling processability (drill wear rate).

[0007] In view of the above circumstances, the present invention is made in order to provide a prepreg with excellent drilling machinability (low drill wear rate) and low coefficient of thermal expansion, and a metal foil laminate and wiring board using the prepreg.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: International Patent Publication No. 2013 / 146700

[0011] Patent Document 2: International Patent Publication No. 2013 / 047203 Summary of the Invention

[0012] The inventors conducted dedicated research to solve the above-mentioned problems and found that the above-mentioned problems could be solved by the following configuration. Based on this insight, they conducted further research and completed the present invention.

[0013] One technical solution of the present invention relates to a prepreg comprising: a thermosetting resin composition or a semi-cured product of the thermosetting resin composition; and glass cloth, wherein the thermosetting resin composition contains molybdenum compound particles (A) and maleimide compound (B), and the glass cloth contains, relative to the total composition of the glass cloth: 45-55% by mass of SiO2; 20-30% by mass of Al2O3; less than 3.0% by mass of MgO; and 10-15% by mass of P2O5.

[0014] One technical solution of the present invention relates to a metal foil laminate comprising: an insulating layer containing the prepreg and a cured material; and a metal layer.

[0015] One technical solution of the present invention relates to a wiring board comprising: an insulating layer comprising a cured prepreg; and wiring. Attached Figure Description

[0016] Figure 1 This is a schematic diagram illustrating the drilling process used to determine the drill bit wear rate in one embodiment of the present invention.

[0017] Figure 2 This is a schematic cross-sectional view showing the structure of a prepreg according to an embodiment of the present invention.

[0018] Figure 3 This is a schematic cross-sectional view illustrating the structure of a metal foil laminate according to an embodiment of the present invention.

[0019] Figure 4 This is a schematic cross-sectional view showing the structure of a wiring board according to an embodiment of the present invention. Detailed Implementation

[0020] The following describes the embodiments of the present invention, but the present invention is not limited to these embodiments.

[0021] <Prepreg>

[0022] The prepreg of this embodiment includes: a thermosetting resin composition or a semi-cured product of the thermosetting resin composition; and glass cloth, wherein the thermosetting resin composition contains molybdenum compound particles (A) and maleimide compound (B), and the glass cloth contains, relative to the total composition of the glass cloth, 45-55% by mass of SiO2; 20-30% by mass of Al2O3; less than 3.0% by mass of MgO; and 10-15% by mass of P2O5.

[0023] The prepreg of this embodiment with this configuration has excellent drilling processability and low coefficient of thermal expansion. Therefore, the metal foil laminate and wiring board obtained using the prepreg of this embodiment have a lower drill wear rate and can also suppress warping.

[0024] It should be noted that, in this specification, excellent drilling performance refers to a low drill bit wear rate. The drill bit wear rate can be measured as follows: Figure 1 The method described is used for measurement. Specifically, two evaluation substrates (metal foil laminates) 11 are overlapped, an entry board 16 is placed on top, and 10,000 holes are drilled using a drill bit 15, extending from the entry board 16 to the evaluation substrate (metal foil laminate) 11. The wear rate of the drill bit's cutting edge can be determined based on the cutting edge size (area) of the drill bit after drilling and the cutting edge size (area) of the drill bit before drilling. More specifically, the measurement can be performed using the method described in the examples.

[0025] The following is a detailed description of each component of the prepreg involved in this embodiment.

[0026] [Thermosetting resin composition]

[0027] The thermosetting resin composition (hereinafter also referred to as the "resin composition") involved in this embodiment contains molybdenum compound particles (A) and maleimide compound (B).

[0028] (Molybdenum compound particles (A))

[0029] Molybdenum compound particles (A) are a component used to further improve drilling machinability (low wear rate). In a preferred embodiment, the molybdenum compound particles (A) comprise molybdenum compound particles (A-1) that have been surface-treated (surface modified) with a surface treatment agent. At least a portion of the surface of the molybdenum compound particles (A-1) has been surface-treated with a surface treatment agent. By including molybdenum compound particles (A-1) that have been surface-treated (surface modified) with a surface treatment agent in the molybdenum compound particles (A), the adhesive strength of the cured resin composition can be improved. It should be noted that, in this specification, the adhesive strength of the cured resin composition refers to the adhesive strength to a metal layer (e.g., copper foil).

[0030] Here, "surface treatment agent" refers to a substance that alters at least one of the properties of a substance's surface, such as its adhesion, reactivity, or compatibility with other substances. For example, surface treatment agents include coupling agents such as silane coupling agents.

[0031] Furthermore, the statement “molybdenum compound particles (A) include molybdenum compound particles (A-1) that have been surface-treated with a surface treatment agent” has two meanings.

[0032] The first meaning refers to the fact that the molybdenum compound particles (A) include molybdenum compound particles (A-1) that have already been surface-treated with a surface-treatment agent. The first meaning also envisions the use of a pretreatment method (premixing method) in the manufacture of the resin composition.

[0033] On the other hand, the second meaning refers to the fact that the molybdenum compound particles (A) include molybdenum compound particles (A-1), that is, although the molybdenum compound particles (A-1) have not yet undergone surface treatment, they may be surface treated by a coexisting surface treatment agent. The second meaning envisions the use of an integral blending method in the manufacture of the resin composition.

[0034] Molybdenum compound particles (A) are not particularly limited, and examples include molybdenum trioxide particles, molybdenum dioxide particles, zinc molybdate particles, ammonium molybdate particles, magnesium molybdate particles, calcium molybdate particles, barium molybdate particles, sodium molybdate particles, potassium molybdate particles, phosphomolybdate particles, ammonium phosphomolybdate particles, sodium phosphomolybdate particles, molybdate silicon particles, and other molybdenum oxides and molybdate compounds; as well as molybdenum boride particles, molybdenum disilicide particles, molybdenum nitride particles, molybdenum carbide particles, and other molybdenum compounds. These can be used alone or in combination of two or more.

[0035] Among these, zinc molybdate, calcium molybdate, and magnesium molybdate are preferred from the perspectives of chemical stability, moisture resistance, and insulation.

[0036] The surface treatment agent preferably comprises at least one compound selected from the group consisting of fluorene compounds, phenylaminosilane compounds, styrylsilane compounds, triphenylphosphine compounds, methacryloxysilane compounds, epoxysilane compounds, isocyanate compounds, vinylsilane compounds, and organosilicon compounds. Accordingly, the adhesive strength of the cured resin composition can be further improved. It should be noted that the compounds listed above are all silane coupling agents.

[0037] The 50% volume average particle size (D) of molybdenum compound particles (A) 50 The particle size is preferably 0.1 μm or more and 2.0 μm or less, more preferably 0.1 μm or more and 1.0 μm or less. This is achieved by reducing the 50% volume average particle size (D) of the molybdenum compound particles (A).50 By setting the particle size to 0.1 μm or larger, the adhesive strength of the cured resin composition can be improved. Furthermore, by setting the 50% volume average particle size (D) of the molybdenum compound particles (A) to 0.1 μm or larger, the adhesive strength of the cured resin composition can be improved. 50 A particle size of 2.0 μm or less improves formability. Here, "50% volume average particle size" refers to the particle size (D50) at which the cumulative value of the particle size distribution measured using a particle size distribution measuring device based on laser scattering and diffraction reaches 50%. 50 ).

[0038] The 90% volume average particle size (D) of molybdenum compound particles (A) 90 Preferably, the particle size is 1.5 μm or less, more preferably 1.3 μm or less. Here, "90% volume average particle size" refers to the particle size (D0) at which the cumulative value of the particle size distribution measured using a particle size distribution measuring device based on laser scattering and diffraction reaches 90%. 90 ).

[0039] (maleimide compound (B))

[0040] The use of maleimide compound (B) is not particularly limited to any compound having a maleimide group within its molecule. Specifically, examples of maleimide compound (B) include: monofunctional maleimide compounds having one maleimide group within their molecule; polyfunctional maleimide compounds having two or more maleimide groups within their molecule; and modified maleimide compounds. Examples of modified maleimide compounds include: modified maleimide compounds in which a portion of the molecule is modified by an amine compound; modified maleimide compounds in which a portion of the molecule is modified by an organosilicon compound; and modified maleimide compounds in which a portion of the molecule is modified by both an amine compound and an organosilicon compound.

[0041] More specifically, examples include: maleimide compounds having two or more N-substituted maleimide groups within one molecule; maleimide compounds having an indane structure; maleimide compounds having at least one of an alkyl group having six or more carbon atoms and an alkylene group having six or more carbon atoms; and maleimide compounds having a benzene ring within one molecule. Further specifically, examples include: compounds represented by formula (1) below, and compounds represented by formula (2) below.

[0042]

[0043] In equation (1), s represents 1 to 5. This s is the average number of repetitions (degree of aggregation).

[0044]

[0045] The maleimide compound (B) used in this embodiment can be a commercially available product, such as BMI-4000, BMI-2300, BMI-TMH, BMI-4000, BMI-5100 manufactured by Daiwa Chemical Industries, Ltd.; MIR-3000-70MT, MIR-5000 manufactured by Nippon Kayaku Co., Ltd.; BMI-689, BMI-1500, BMI-3000J, BMI-5000 manufactured by Designer Molecules Inc.

[0046] Maleimide compound (B) can be used alone or in combination with two or more maleimide compounds as described above.

[0047] (Benzoxazine compound (C))

[0048] The thermosetting resin composition preferably contains a benzoxazine compound (C). By including a benzoxazine compound (C) in the resin composition, the bond strength of the cured resin composition can be improved, and the coefficient of thermal expansion can be reduced more reliably. The benzoxazine compound (C) is not particularly limited as long as it is a compound having at least one benzoxazine ring. Examples include benzoxazine compounds having an alkenyl group within the molecule.

[0049] Benzoxazine compounds containing an alkenyl group within the molecule not only have an alkenyl group but also a benzoxazine group. The alkenyl group is not particularly limited, and examples include alkenyl groups having 2 to 6 carbon atoms. Specifically, examples of the alkenyl group include vinyl, allyl, propenyl, and butenyl, among which allyl and propenyl are preferred, and allyl is more preferred. That is, the benzoxazine compound (C) preferably includes an allyl-containing benzoxazine compound (C-1), as including this allyl-containing benzoxazine compound (C-1) readily reduces the coefficient of thermal expansion. The allyl-containing benzoxazine compound (C-1) is a benzoxazine compound having at least one allyl group.

[0050] The benzoxazine group is not particularly limited, and examples include the benzoxazine group shown in formula (3) and the benzoxazine group shown in formula (4). As a benzoxazine compound (C), not only can benzoxazine compounds having the benzoxazine group shown in formula (3) and the benzoxazine compound having the benzoxazine group shown in formula (4) be listed, but also benzoxazine compounds having the benzoxazine group shown in formula (3) and the benzoxazine group shown in formula (4) be listed.

[0051]

[0052] In formula (3), R1 represents allyl, and a represents 1 to 4. a is the average value of the degree of substitution of R1, which is 1 to 4, preferably 1.

[0053]

[0054] In formula (4), R2 represents allyl.

[0055] As an allyl benzoxazine compound (C-1), more specifically, benzoxazine compounds having the structures shown in formulas (3) and (4) are exemplified, such as benzoxazine compounds having the structures shown in formulas (5) to (7) below. More specifically, compounds shown in formula (8) below are exemplified.

[0056]

[0057]

[0058]

[0059]

[0060] In the formula (8), R3 and R4 represent allyl, Y represents alkylene, and b and c each independently represent 1 to 4.

[0061] The alkylene group is not particularly limited, and examples include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, eicosyl, and hexadecyl. Among them, methyl is preferred.

[0062] In equation (8), b is the average degree of substitution of R3, which is 1 to 4, preferably 1. Furthermore, in equation (8), c is the average degree of substitution of R4, which is 1 to 4, preferably 1.

[0063] Benzoxazine compounds (C) can also be commercially available, such as Pd-type benzoxazine compounds manufactured by Shikoku Chemical Industry Co., Ltd., or "ALP-d" manufactured by Shikoku Chemical Industry Co., Ltd.

[0064] As a benzoxazine compound (C), the benzoxazine compounds exemplified above can be used alone, or two or more can be used in combination.

[0065] (Elastomer (D))

[0066] The thermosetting resin composition preferably contains an elastomer (D) comprising at least one of a high molecular weight substance (D-1) with a weight average molecular weight of 10,000 or more and 900,000 or less, and a core-shell rubber (D-2).

[0067] It is believed that by including a high molecular weight substance (D-1) with a weight-average molecular weight (Mw) of 10,000 or more and 900,000 or less in the thermosetting resin composition, a lower coefficient of thermal expansion can be obtained in the cured product. More preferably, the high molecular weight substance (D-1) has a weight-average molecular weight (Mw) of 10,000 or more and 600,000 or less. In this specification, the weight-average molecular weight is simply a molecular weight obtained by conventional molecular weight determination methods; specifically, values ​​measured using gel permeation chromatography (GPC) can be cited.

[0068] The high molecular weight material (D-1) preferably comprises at least one of an acrylic resin and a styrene copolymer with a weight average molecular weight of 10,000 or more and 900,000 or less. By including at least one of an acrylic resin and a styrene copolymer in the high molecular weight material (D-1), the coefficient of thermal expansion can be reduced.

[0069] As a specific acrylic resin in this embodiment, it is preferred to have the structure shown in the following formulas (9), (10) and (11).

[0070]

[0071]

[0072]

[0073] In the above equations (9) to (11), x, y, and z represent mole fractions and satisfy x + y + z ≤ 1, 0 < x ≤ 0.2, 0.6 ≤ y ≤ 0.95, and 0.05 ≤ z ≤ 0.2.

[0074] In the above formula (10), R5 is a hydrogen atom or a methyl group, and R6 includes at least one of a glycidyl group and an epoxidized alkyl group among a hydrogen atom, an alkyl group, a glycidyl group and an epoxidized alkyl group.

[0075] In the above formula (11), R7 is a hydrogen atom or a methyl group, and R8 is Ph (phenyl), -COOCH2Ph ​​or -COO(CH2)2Ph.

[0076] Preferably, the main chain of the acrylic resin has at least one structure represented by formula (9), at least one structure represented by formula (10), and at least one structure represented by formula (11).

[0077] When the main chain of the acrylic resin has the structures shown in formulas (9), (10), and (11), the configuration order of the structures shown in formulas (9), (10), and (11) is not particularly limited. In this case, in the main chain of the acrylic resin, the structure shown in formula (9) can be continuous or discontinuous; and the structure shown in formula (10) can be continuous or discontinuous; and the structure shown in formula (11) can be continuous or discontinuous.

[0078] Here, we will further explain the meaning of R6 in formula (10) as including at least one of glycidyl group and epoxidized alkyl group among hydrogen atom, alkyl group, glycidyl group and epoxidized alkyl group. As a premise, there is one R6 in a structure shown by formula (10). We will explain the cases where the acrylic resin has only one structure shown by formula (10) and the cases where it has more than two structures.

[0079] In the former case, i.e., when the acrylic resin has a structure as shown in formula (10), R6 is a glycidyl group or an epoxidized alkyl group.

[0080] In the latter case, when the acrylic resin has two or more structures represented by formula (10), at least one R6 in the structure represented by formula (10) is a glycidyl group or an epoxidized alkyl group, and the remaining R6 in the structures represented by formula (10) is a hydrogen atom or an alkyl group. Since at least one R6 in the structure represented by formula (10) is a glycidyl group or an epoxidized alkyl group, it is also possible for all R6 in the structures represented by formula (10) to be glycidyl groups or epoxidized alkyl groups.

[0081] The structure shown in formula (11) has Ph (phenyl), -COOCH2Ph, and -COO(CH2)2Ph. Since Ph, -COOCH2Ph, and -COO(CH2)2Ph have thermal stability, the strength of the cured resin composition can be improved, and the heat resistance of the laminate (metal foil laminate and wiring board) can be improved.

[0082] The styrene copolymers that can be used in this embodiment are copolymers obtained by polymerizing two or more monomers containing styrene monomers. There are no particular limitations as long as the weight average molecular weight is within the above range. More specifically, examples include: methylstyrene (ethylene / butene) methylstyrene block copolymers; methylstyrene (ethylene-ethylene / propylene) methylstyrene block copolymers; styrene-isoprene block copolymers; hydrogenated styrene-isoprene-styrene block copolymers; styrene (ethylene / butene) styrene block copolymers; styrene (ethylene-ethylene / propylene) styrene block copolymers; methylstyrene (styrene / butadiene random copolymer block) methylstyrene copolymers, styrene (styrene / butadiene random copolymer block) styrene copolymers, styrene-butadiene-styrene block copolymers, etc.; styrene-isobutylene-styrene block copolymers; styrene (butadiene / butene) styrene block copolymers; and at least a portion of their hydrogenated hydrides, etc.

[0083] Commercially available products can also be used as the styrene copolymers, such as Tuftec P1500, Tuftec H1221, Tuftec H1041, Tuftec H1517, Tuftec M1913, Tuftec M1981, etc., manufactured by Asahi Kasei Corporation.

[0084] It should be noted that the high molecular weight substance (D-1) does not contain maleimide compounds (B), benzoxazine compounds (C), or core-shell rubber (D-2).

[0085] The core-shell rubber (D-2) that can be used in this embodiment is an aggregate of rubber particles, each of which has a core-shell multilayer structure. The rubber particles are formed by a core and a shell. At least one of the core and shell is elastic. By including this core-shell rubber (D-2) in the resin composition, the impact resistance, thermal shock resistance, and low thermal expansion of the cured product can be improved without compromising heat resistance.

[0086] Preferably, the core-shell rubber (D-2) contains silicone in at least one of the core and shell. This further improves thermal shock resistance. In other words, compared to the case without silicone, impact resistance is improved even at lower temperatures.

[0087] The core can help improve the toughness of the cured resin composition. The core is a particulate rubber. The rubber can be a copolymer or a homopolymer. There are no particular limitations on the polymer constituting the core, but examples include: silicone / acrylic polymers; acrylic polymers; silicone polymers; butadiene polymers; and isoprene polymers, etc.

[0088] The shell is readily compatible with maleimide compounds (B) and benzoxazine compounds (C), and contributes to improved adhesive strength of the cured resin composition. The shell is present on the surface of the core. The shell has multiple grafted chains. Each grafted chain has a fixed end bonded to the surface of the core and a free end. The grafted chains can be bonded to copolymers or homopolymers. The polymer constituting the shell is not particularly limited; examples include acrylic copolymers, polymethyl methacrylate, and polystyrene.

[0089] The 50% volume average particle size (D) of core-shell rubber (D-2) 50 The particle size is preferably 0.01 μm or more and 0.5 μm or less, more preferably 0.05 μm or more and 0.3 μm or less. This is achieved by reducing the 50% volume average particle size (D) of the core-shell rubber (D-2) to a certain value. 50 A particle size of 0.01 μm or larger can further improve the impact resistance of the cured material. This is achieved by reducing the 50% volume average particle size (D) of the core-shell rubber (D-2) to above 0.01 μm. 50 With a particle size below 0.5 μm, the core-shell rubber (D-2) is easily and uniformly dispersed in the resin composition, and consequently, it is also easily and uniformly dispersed in the cured product. Here, "50% volume average particle size" refers to the particle size (D0.5) at which the cumulative value of the particle size distribution reaches 50% as measured by a particle size distribution measuring device based on laser scattering and diffraction. 50 ).

[0090] (Inorganic filler material (E))

[0091] The resin composition of this embodiment may contain inorganic filler material (E) other than molybdenum compound particles (A) as needed, without impairing the effects of the present invention. That is, in this embodiment, the inorganic filler material (E) does not contain molybdenum compound particles (A). It is believed that when the resin composition contains inorganic filler material (E), the low thermal expansion properties of the cured resin composition can be improved, etc.

[0092] The inorganic filler (E) is not particularly limited to any inorganic filler that can be used as an inorganic filler in the resin composition. Examples of inorganic fillers (E) include: metal oxide particles, metal hydroxide particles, nitride particles, titanate particles, anhydrous magnesium carbonate particles, magnesium carbonate particles, calcium carbonate particles, quartz glass particles, talc particles, aluminum borate particles, and barium sulfate particles. Examples of metal oxide particles include: silica particles, alumina particles, titanium oxide particles, magnesium oxide particles, and mica particles. Examples of silica particles include: pulverized silica, molten spherical silica, and other spherical silica. Examples of metal hydroxide particles include: boehmite particles, magnesium hydroxide particles, and aluminum hydroxide particles. Examples of nitride particles include: aluminum nitride particles and boron nitride particles. Examples of titanate particles include: barium titanate particles, strontium titanate particles, calcium titanate particles, and aluminum titanate particles.

[0093] The inorganic filler material (E) preferably comprises at least one selected from the group consisting of silica particles, aluminum hydroxide particles, talc particles, magnesium hydroxide particles and boehmite particles.

[0094] Furthermore, the inorganic filler material (E) can be used alone, as described above, or in combination with two or more other inorganic fillers. When using two or more of the aforementioned inorganic fillers in combination, silica particles can be combined with one or more inorganic fillers other than silica particles.

[0095] The inorganic filler material (E) can be a surface-treated inorganic filler material or an untreated inorganic filler material. Furthermore, examples of surface treatment include treatment with a silane coupling agent.

[0096] (content)

[0097] The content of molybdenum compound particles (A) is preferably 0.1 to 40 parts by mass, more preferably 0.1 to 35 parts by mass, and even more preferably 5 to 30 parts by mass, relative to 100 parts by mass of the resin component in the resin composition. When the content of molybdenum compound particles (A) is 0.1 parts by mass or more relative to 100 parts by mass of the resin component in the resin composition, the reduction in drilling processability can be suppressed. On the other hand, when the content of molybdenum compound particles (A) is 40 parts by mass or less relative to 100 parts by mass of the resin component in the resin composition, the etching ratio of the descaling solution can be reduced. In this specification, "resin component" refers to the resin components contained in the resin composition. For example, if the resin composition contains maleimide compound (B) and benzoxazine compound (C), it refers to their total; furthermore, if the resin composition contains elastomer (D) in addition to maleimide compound (B) and benzoxazine compound (C), it refers to their total (B + C + D).

[0098] The content of maleimide compound (B) relative to the total amount of resin components in the resin composition is preferably 15-75% by mass, more preferably 30-50% by mass. When the content of maleimide compound (B) is 15% by mass or more relative to the total amount of resin components in the resin composition, the coefficient of thermal expansion can be reduced. When the content of maleimide compound (B) is 75% by mass or less relative to the total amount of resin components in the resin composition, the reduction in the adhesive strength of the cured resin composition can be suppressed.

[0099] When the thermosetting resin composition contains a benzoxazine compound (C), the content of the benzoxazine compound (C) is preferably 10 to 50% by mass, more preferably 13 to 30% by mass, relative to the total amount of resin components in the resin composition. When the content of the benzoxazine compound (C) is 10% by mass or less relative to the total amount of resin components in the resin composition, the reduction in the adhesive strength of the cured resin composition can be suppressed. When the content of the benzoxazine compound (C) is 50% by mass or less relative to the total amount of resin components in the resin composition, the coefficient of thermal expansion can be reduced.

[0100] When the thermosetting resin composition contains a benzoxazine compound (C), the mass ratio (C / B) of the benzoxazine compound (C) to the maleimide compound (B) is preferably 0.2 to 1.0, more preferably 0.3 to 0.9. By setting the above-mentioned mass ratio (C / B) to 0.3 or more, the decrease in the adhesive strength of the cured resin composition can be suppressed. Furthermore, the decrease in drilling workability can also be suppressed. By setting the above-mentioned mass ratio (C / B) to 1.0 or less, the decrease in the glass transition temperature (Tg) can be suppressed.

[0101] When the thermosetting resin composition contains an elastomer (D), the content of elastomer (D) is preferably 5 to 40% by mass, more preferably 10 to 30% by mass, relative to the total amount of resin components in the resin composition. When the content of elastomer (D) is 5% by mass or more relative to the total amount of resin components in the resin composition, the coefficient of thermal expansion can be reduced. When the content of elastomer (D) is 40% by mass or less relative to the total amount of resin components in the resin composition, the moldability can be improved.

[0102] As described above, the resin composition may contain inorganic filler (E). When the resin composition contains inorganic filler (E), the content of inorganic filler (E) is preferably 80 to 180 parts by mass, more preferably 90 to 170 parts by mass, relative to 100 parts by mass of the resin component in the resin composition (excluding the molybdenum compound particles (A) and inorganic filler (E)). By having an inorganic filler (E) content of 80 to 180 parts by mass relative to 100 parts by mass of the resin component in the resin composition, the coefficient of thermal expansion can be reduced. Furthermore, it is possible to suppress the reduction in moldability.

[0103] Furthermore, when the resin composition contains inorganic filler (E), the content of molybdenum compound particles (A) is preferably 0.1 to 30% by mass, more preferably 1 to 15% by mass, relative to the total content of molybdenum compound particles (A) and inorganic filler (E) (100% by mass). By making the content of molybdenum compound particles (A) 0.1% by mass or more relative to the total content of molybdenum compound particles (A) and inorganic filler (E) (100% by mass), the reduction in drilling machinability can be suppressed. By making the content of molybdenum compound particles (A) 30% by mass or less, the etching ratio of the desizing solution can be reduced.

[0104] The content of the thermosetting resin composition in the prepreg of this embodiment is preferably 35-80% by mass, more preferably 40-75% by mass, relative to the total amount of components in the prepreg. Since the content of the thermosetting resin composition in the prepreg is 35-80% by mass relative to the total amount of components in the prepreg, the prepreg of this embodiment can more reliably achieve the above-mentioned effects (excellent drilling processability, low coefficient of thermal expansion).

[0105] (Other ingredients)

[0106] The resin composition may also contain other components (other components) besides those described above, without impairing the effects of the present invention. Examples of other components include, for instance, organic components other than those described in (B) to (D), flame retardants, reaction initiators, curing accelerators, catalysts, polymerization retardants, polymerization inhibitors, dispersants, homogenizers, coupling agents, defoamers, antioxidants, heat stabilizers, antistatic agents, ultraviolet absorbers, dyes or pigments, and additives such as lubricants.

[0107] As described above, the resin composition according to this embodiment may also contain organic components other than components (B) to (D) mentioned above. These organic components may be, for example, compounds that react with at least one of components (B) to (D) mentioned above, or compounds that do not react. Specifically, examples of these organic components include epoxy resins, cyanate ester compounds, and reactive ester compounds.

[0108] The epoxy resin is not particularly limited, and examples include bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, aralkyl epoxy resin, phenolic varnish type epoxy resin, alkylphenolic varnish type epoxy resin, biphenyl type epoxy resin, biphenylene type epoxy resin, bisphenol type epoxy resin, triphenylmethane type epoxy resin, naphthalene type epoxy resin, dicyclopentadiene type epoxy resin, epoxidation products of condensates of phenols and aromatic aldehydes with phenolic hydroxyl groups, triglycidyl isocyanate, alicyclic epoxy resin, etc. Among these, biphenylene type epoxy resin and naphthalene type epoxy resin are preferred. Depending on the circumstances, one type may be used alone, or two or more types may be used in combination.

[0109] As described above, the resin composition of this embodiment may also contain a reaction initiator. The reaction initiator is not particularly limited as long as it can promote the curing reaction of the resin composition; examples include peroxides and organic azo compounds. Examples of peroxides include α,α'-di(tert-butylperoxy)diisopropylbenzene (PBP), 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, and benzoyl peroxide. Examples of organic azo compounds include azobisisobutyronitrile. Furthermore, metal salts of carboxylic acids may be used in combination as needed. This further promotes the curing reaction. A single reaction initiator may be used, or two or more may be used in combination.

[0110] As described above, the resin composition involved in this embodiment may contain a curing accelerator. The curing accelerator is not particularly limited as long as it can promote the curing reaction of the resin composition. Specifically, examples of curing accelerators include: imidazoles and their derivatives, organophosphorus compounds, amines such as secondary and tertiary amines, quaternary ammonium salts, organoboron compounds, and metal soaps. Examples of imidazoles include: 2-ethyl-4-methylimidazolium (2E4MZ), 2-methylimidazolium, 2-phenyl-4-methylimidazolium, 2-phenylimidazolium, and 1-benzyl-2-methylimidazolium. Examples of organophosphorus compounds include: triphenylphosphine, diphenylphosphine, phenylphosphine, tributylphosphine, and trimethylphosphine. Furthermore, examples of amines include: dimethylbenzylamine, triethylenediamine, triethanolamine, and 1,8-diazabicyclo(5,4,0)undecene-7 (DBU). Furthermore, examples of quaternary ammonium salts include tetrabutylammonium bromide. Furthermore, examples of the organoboron compounds include tetraphenylboron salts such as 2-ethyl-4-methylimidazole tetraphenylborate, and tetra-substituted phosphonium tetra-substituted borates such as tetraphenylphosphonium ethyltriphenylborate. Additionally, the metal soap refers to a fatty acid metal salt, which can be a linear or cyclic fatty acid metal salt. Specifically, examples of the metal soap include linear aliphatic metal salts with 6 to 10 carbon atoms and cyclic aliphatic metal salts. More specifically, examples of the metal soap include linear fatty acids such as stearic acid, lauric acid, ricinoleic acid, and octanoic acid, or cyclic fatty acids such as naphthenic acids, and aliphatic metal salts formed from metals such as lithium, magnesium, calcium, barium, copper, and zinc. Examples of the metal soap include zinc octanoate. The curing accelerator can be used alone or in combination with two or more.

[0111] [Glass cloth]

[0112] The glass cloth contained in the prepreg of this embodiment is relative to the total composition of the glass cloth, comprising: 45-55% by mass of SiO2, 20-30% by mass of Al2O3, less than 3.0% by mass of MgO, and 10-15% by mass of P2O5.

[0113] By using this glass cloth, the prepreg in this embodiment can have a lower coefficient of thermal expansion and a lower drill bit wear rate.

[0114] In the glass cloth of this embodiment, if SiO2 is less than 45% by mass, it is difficult to obtain sufficient low dielectric properties; if it exceeds 55% by mass, the viscosity increases during spinning, making it difficult to fiberize. A more preferred content of SiO2 in the total amount of glass cloth is 47-53% by mass.

[0115] In the glass cloth of this embodiment, if Al2O3 is less than 20% by mass, the water resistance deteriorates; if it exceeds 30% by mass, the spinnability deteriorates and the dielectric constant increases. A more preferred content of Al2O3 in the total amount of glass cloth is 22 to 28% by mass.

[0116] In the glass cloth of this embodiment, if MgO exceeds 3% by mass, the water resistance deteriorates, and it is difficult to obtain sufficient low dielectric properties. The lower limit of the MgO content is not particularly limited, but from the viewpoint of homogenizing the glass fibers, 0.5% or more is preferred. A more preferred MgO content in the total amount of glass cloth is 0.5% to 2.8% by mass.

[0117] In the glass cloth of this embodiment, if P2O5 is less than 10% by mass, it is difficult to sufficiently suppress the hardness caused by Al2O3; if it exceeds 15% by mass, the water resistance and weather resistance may deteriorate. A more preferred content of P2O5 in the total amount of glass cloth is 10 to 14% by mass.

[0118] In addition to the components described above, the glass cloth of this embodiment may also contain approximately 0.01 to 0.05% by mass of CaO. By including CaO in the glass cloth within this range, water resistance can be improved, and the manufacturability of the glass cloth can be improved by reducing the melt viscosity of the molten glass.

[0119] The glass cloth in this embodiment may also contain approximately 0.01 to 5% by mass of Na2O. By including Na2O in the glass cloth within this range, the dielectric loss factor (Df) can be further reduced, and the manufacturability of the glass cloth can be improved by reducing the melt viscosity of the molten glass.

[0120] Furthermore, the glass cloth of this embodiment may also contain Li₂O and / or K₂O, and their combined content relative to the total composition of the glass cloth is preferably in the range of 0.03 to 0.15% by mass, more preferably in the range of 0.04 to 0.10% by mass. It is believed that by including Li₂O and / or K₂O in the glass cloth within this range, a low dielectric constant can be maintained, and the manufacturability of the glass cloth can be improved by reducing the melt viscosity of the molten glass.

[0121] The glass cloth in this embodiment may also contain about 0.01 to 2% by mass of Fe2O3. By including Fe2O3 in the glass cloth within this range, coloration of the glass cloth can be suppressed, and the manufacturability of the glass cloth can be improved by enhancing the defoaming properties of the molten glass.

[0122] The glass cloth in this embodiment may also contain about 0.01 to 10% by mass of ZnO. By including ZnO in the glass cloth within this range, thermal expansion can be suppressed.

[0123] The glass cloth in this embodiment may also contain 0.01 to 0.10% by mass of ZrO2. By including ZrO2 in the glass cloth within this range, the alkali resistance of the glass cloth can be improved.

[0124] On the other hand, the glass cloth of this embodiment preferably contains substantially no B2O3, F2, and TiO2 (i.e., the content is less than 0.01% by mass), and more preferably contains none at all (i.e., the content is 0% by mass). By substantially containing none of these components, the elastic modulus of the glass cloth can be maintained at a higher level, and the acid resistance of the glass cloth can be improved.

[0125] The proportions of the aforementioned components in the glass cloth of this embodiment can be determined using a fluorescence X-ray analysis apparatus. Specifically, Rh can be irradiated with X-rays under a vacuum atmosphere, and analysis can be performed with an analysis diameter of 20 mmφ. Alternatively, ICP emission spectroscopy analysis can also be used for determination.

[0126] The glass cloth in this embodiment can also be a surface-treated glass cloth. As a surface treatment agent, a silane coupling agent having functional groups such as vinyl, styrene, methacryloyl, acryloyl, phenylamino is preferably used.

[0127] The glass cloth in this embodiment is preferably a glass cloth that has undergone further flattening processing. Specifically, flattening processing can be exemplified by continuously applying appropriate pressure to the glass cloth using pressure rollers to compress the yarn into a flat shape. The thickness of the glass cloth in this embodiment is not particularly limited; for example, a glass cloth of approximately 0.02 to 0.1 mm can be used without particular restriction.

[0128] In this embodiment, the glass cloth preferably accounts for about 20-65% by mass of the total amount of prepreg. By including the glass cloth in this proportion, the prepreg of this embodiment can more reliably achieve the above-mentioned effects. A more preferred proportion of glass cloth is 25-60% by mass.

[0129] [Prepreg Manufacturing Method]

[0130] Next, the method for obtaining the prepreg of this embodiment will be described. Figure 2 This is a schematic cross-sectional view showing an example of the prepreg 1 according to an embodiment of the present invention.

[0131] like Figure 2 As shown, the prepreg 1 according to this embodiment includes: the thermosetting resin composition or the semi-cured product of the thermosetting resin composition 2; and glass cloth 3. The prepreg 1 includes: the thermosetting resin composition or the semi-cured product of the thermosetting resin composition 2; and glass cloth 3 present in the thermosetting resin composition or the semi-cured product of the thermosetting resin composition 2.

[0132] It should be noted that, in this embodiment, a semi-cured substance is a substance that has cured a thermosetting resin composition to a state where it can still be further cured. That is, a semi-cured substance is a substance that causes the thermosetting resin composition to be in a semi-cured state (benzene curing). For example, if the thermosetting resin composition is heated, its viscosity initially gradually decreases, then begins to cure, and then gradually increases. In this case, the state from the time the viscosity begins to increase until complete curing can be listed as a semi-cured substance.

[0133] Furthermore, the prepreg obtained using the thermosetting resin composition according to this embodiment can be, as described above, a prepreg containing a semi-cured product of the thermosetting resin composition, or a prepreg containing an uncured thermosetting resin composition. That is, it can be a prepreg containing a semi-cured product of the thermosetting resin composition (the thermosetting resin composition of stage B) and glass cloth, or a prepreg containing the thermosetting resin composition before curing (the thermosetting resin composition of stage A) and glass cloth. The thermosetting resin composition or the semi-cured product of the thermosetting resin composition can be a substance obtained by drying or heating the thermosetting resin composition.

[0134] In the manufacture of prepregs, the thermosetting resin composition 2 is mostly formulated into a varnish-like form for impregnation into the substrate, i.e., glass cloth 3, used to form the prepreg. That is, the thermosetting resin composition 2 is usually a resin varnish formulated into a varnish-like form. This varnish-like thermosetting resin composition (resin varnish) can be obtained, for example, by mixing a maleimide compound (B) with other resin components (benzoxazine compound (C) and elastomer (D), etc.) as needed, and then adding molybdenum compound particles (A) and inorganic filler (E), etc., as needed, and mixing them together.

[0135] First, the components of the thermosetting resin composition that are soluble in organic solvents, namely maleimide compound (B) and other resin components (benzoxazine compound (C) and elastomer (D), etc.) added as needed, are added to the organic solvent and dissolved. Heating may be performed at this time if necessary. Then, components that are insoluble in organic solvents (molybdenum compound particles (A) and inorganic filler material (E), etc., used as needed) are added, and dispersed to a specified dispersion state using a disperser or the like, thereby preparing a varnish-like thermosetting resin composition. The organic solvent used here is not particularly limited as long as it can dissolve the components of the thermosetting resin composition that are soluble in organic solvents and does not hinder the curing reaction. Examples of suitable organic solvents include toluene and methyl ethyl ketone (MEK).

[0136] The method for manufacturing the prepreg 1 is not particularly limited, but examples include: impregnating a thermosetting resin composition 2, which is prepared into a varnish-like state, into a glass cloth 3 and then drying it. The thermosetting resin composition 2 is impregnated into the glass cloth 3 by impregnation and coating, etc. Impregnation can be repeated multiple times as needed. In this case, the final desired composition and impregnation amount can also be adjusted by repeatedly impregnating with multiple resin compositions of different compositions and / or concentrations.

[0137] Glass cloth 3 impregnated with a thermosetting resin composition (resin varnish) 2 is heated under desired heating conditions (e.g., heating at 80°C or higher and 180°C or lower for 1 minute or more and 10 minutes or less). Heating yields a prepreg 1 in a pre-cured (stage A) or semi-cured (stage B) state. It should be noted that the heating causes the organic solvent to evaporate from the resin varnish, thus reducing or eliminating the organic solvent.

[0138] The prepreg of this embodiment combines excellent drillability (low drill bit wear) and a low coefficient of thermal expansion. Therefore, the wiring board having an insulating layer formed using the prepreg of this embodiment exhibits excellent drillability (low drill bit wear) and experiences less warping. Thus, the prepreg of this embodiment is suitable for use in forming an insulating layer disposed on a foil-coated laminate and a wiring board.

[0139] <Metal Foil Coated Laminate>

[0140] Figure 3 This is a schematic cross-sectional view showing an example of the metal foil laminate 11 involved in this embodiment.

[0141] like Figure 3 As shown, the metal foil-coated laminate 11 includes: comprising as follows Figure 2The insulating layer 12 of the cured prepreg 1 shown; and the metal foil 13 laminated together with the insulating layer 12. That is, the metal foil laminate 11 includes: an insulating layer 12 comprising a cured thermosetting resin composition; and a metal foil 13 disposed on the insulating layer 12. The insulating layer 12 may be formed from the cured thermosetting resin composition or from the cured prepreg. The thickness of the metal foil 13 varies depending on the performance requirements of the final wiring board and is not particularly limited. The thickness of the metal foil 13 may be appropriately set according to the required purpose, for example, preferably 0.2 to 70 μm. Examples of the metal foil 13 include copper foil and aluminum foil. In the case of a thinner metal foil, a carrier-supported copper foil with a release layer and a carrier may be used to improve operability.

[0142] As for the method of manufacturing the metal-clad laminate 11, there is no particular limitation as long as the metal-clad laminate 11 can be manufactured. Specifically, a method of manufacturing the metal-clad laminate 11 using prepreg 1 can be cited. As a method, a method can be cited that involves taking a piece of prepreg 1 or stacking several pieces of prepreg 1, and then stacking a metal foil 13 such as copper foil on its upper and lower surfaces or one side surface, and heating and pressing the metal foil 13 and the prepreg 1 to form a laminate integrally, thereby manufacturing a laminate 11 with metal foil on both sides or one side surface. That is, the metal-clad laminate 11 is obtained by stacking metal foil 13 on the prepreg 1 and heating and pressing it. The heating and pressing conditions can be appropriately set according to the thickness of the metal-clad laminate 11 being manufactured or the type of composition of the prepreg 1. For example, the temperature can be set to 170 to 230°C, the pressure to 3 to 5 MPa, and the time to 60 to 150 minutes.

[0143] <Wiring board>

[0144] Figure 4 This is a schematic cross-sectional view showing an example of the wiring board 21 involved in this embodiment.

[0145] like Figure 4 As shown, the wiring board 21 according to this embodiment includes: Figure 2 The insulating layer 12 is used after curing the prepreg 1 shown; and the wiring 14 is formed by laminating the insulating layer 12 together with a portion of the metal foil 13 removed. The insulating layer 12 is formed from the cured prepreg.

[0146] The method for manufacturing the wiring board 21 is not particularly limited as long as it can be manufactured. Specifically, methods such as using the prepreg 1 to manufacture the wiring board 21 can be listed. As a method, for example, etching the metal foil 13 on the surface of the metal foil laminate 11 manufactured as described above to form wiring, thereby manufacturing a wiring board 21 with wiring as a circuit on the surface of the insulating layer 12. That is, the wiring board 21 can be obtained by removing a portion of the metal foil 13 on the surface of the metal foil laminate 11, thereby forming a circuit. In addition, as a method for forming a circuit, besides the methods described above, methods such as forming a circuit by a semi-additive process (SAP) or a modified semi-additive process (MSAP) can be listed.

[0147] Metal foil laminates and wiring boards having an insulating layer comprising a cured prepreg of the present embodiment have the same advantages as the prepreg described above, and are therefore useful for industrial applications.

[0148] This specification discloses various techniques as described above, the main techniques of which are summarized below.

[0149] The prepreg of the first technical solution comprises: a thermosetting resin composition or a semi-cured product of the thermosetting resin composition; and glass cloth, wherein the thermosetting resin composition contains molybdenum compound particles (A) and maleimide compound (B), and the glass cloth contains, relative to the total amount of the glass cloth, 45-55% by mass of SiO2; 20-30% by mass of Al2O3; less than 3.0% by mass of MgO; and 10-15% by mass of P2O5.

[0150] The prepreg of the second technical solution is in the same as the prepreg of the first technical solution, wherein the molybdenum compound particles (A) comprise molybdenum compound particles (A-1) that have been surface-treated with a surface treatment agent.

[0151] In the prepreg of the third technical solution, the cumulative 50% particle size (D) of the molybdenum compound particles (A) in the particle size distribution based on the volume criterion is as follows: 50 The size ranges from 0.1 μm to 2.0 μm.

[0152] In the prepreg of the fourth technical solution, relative to 100 parts by mass of the resin component in the thermosetting resin composition, the content of molybdenum compound particles (A) in the thermosetting resin composition is 0.1 to 40 parts by mass.

[0153] The prepreg of the fifth technical solution, in the prepreg of any one of the first to fourth technical solutions, the thermosetting resin composition further contains a benzoxazine compound (C).

[0154] The prepreg of the sixth technical solution is in the same as that of the fifth technical solution, wherein the benzoxazine compound (C) comprises an allyl benzoxazine compound (C-1).

[0155] In the prepreg of the seventh technical solution, the mass ratio (C / B) of benzoxazine compound (C) to maleimide compound (B) is 0.2 or more and 1.0 or less.

[0156] The prepreg of the eighth technical solution is in the prepreg of any one of the first to seventh technical solutions, wherein the thermosetting resin composition contains an elastomer (D) comprising at least one of a high molecular weight substance (D-1) with a weight average molecular weight of more than 10,000 and less than 900,000 and a core-shell rubber (D-2).

[0157] In the prepreg of the 9th technical solution, the high molecular weight substance (D-1) comprises at least one of an acrylic resin and a styrene copolymer.

[0158] In the prepreg of the 10th technical solution, the content of elastomer (D) in the thermosetting resin composition is 5 to 40% by mass relative to the total amount of resin components in the thermosetting resin composition.

[0159] The prepreg of the 11th technical solution, in the prepreg of any one of the 1st to 10th technical solutions, the thermosetting resin composition further contains an inorganic filler (E), the inorganic filler (E) comprising at least one selected from the group consisting of silica particles, aluminum hydroxide particles, talc particles, magnesium hydroxide particles and boehmite particles.

[0160] In the prepreg of the 12th technical solution, the content of the thermosetting resin composition in the prepreg is 35 to 80% by mass relative to the total amount of components in the prepreg.

[0161] The metal foil laminate of the 13th technical solution includes: an insulating layer of cured material comprising the prepreg of any one of the 1st to 12th technical solutions; and a metal layer.

[0162] The wiring board of the 14th technical solution includes: an insulating layer of cured prepreg containing any one of the 1st to 12th technical solutions; and wiring.

[0163] Example

[0164] The present invention will be further described in detail below through embodiments; however, the scope of the present invention is not limited to these embodiments.

[0165] First, the components used in preparing the thermosetting resin composition in this embodiment will be described.

[0166] [Thermosetting resin composition]

[0167] (Molybdenum compound particles (A))

[0168] • Molybdenum compound particles surface-treated with phenylaminosilane (manufactured by Admatechs Company Limited, product name "Z4SX-A1", D) 50 : 0.8μm, D 90 (1.2μm)

[0169] (maleimide compound (B))

[0170] • The 3,3-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide shown in formula (2) (manufactured by Daiwa Chemical Industry Co., Ltd., product name "BMI-5100")

[0171] (Benzoxazine compound (C))

[0172] ·Benzoxazine compound 1: The benzoxazine compound shown in formula (8) with R3 and R4 being allyl, Y being methyl, and b and c being 1 (manufactured by Shikoku Chemical Industry Co., Ltd., product name "ALP-d")

[0173] ·Benzoxazine compound 2: Pd-type benzoxazine compound (manufactured by Shikoku Chemical Industry Co., Ltd.)

[0174] (Elastomer (D))

[0175] • High molecular weight substance (D-1) (acrylic elastomer): epoxy modified acrylic resin (manufactured by Nagase ChemteX Co., Ltd., product name "PASR-001", weight average molecular weight Mw: 500,000)

[0176] (Epoxy resin)

[0177] • Multifunctional epoxy resin with biphenylene structure (manufactured by Nippon Kayaku Co., Ltd., product name "NC3500")

[0178] (Inorganic filler material (E))

[0179] • Silica particles (manufactured by Yatuma Co., Ltd., product name "SC2050-MTX")

[0180] (Reaction initiator)

[0181] • Organic peroxide: PBP (1,3-bis(butylperoxyisopropyl)benzene; "PERBUTYL P" manufactured by Nippon Yuko Co., Ltd.)

[0182] (Curing accelerator)

[0183] ·2-Ethyl-4-methylimidazolium (manufactured by Shikoku Chemical Industry Co., Ltd., product name "2E4MZ")

[0184] [Glass cloth]

[0185] (1-3 pieces of glass cloth)

[0186] Three types of glass cloths 1 to 3 (0.1 mm thick) with the compositions shown below were prepared. It should be noted that glass cloth 1 is equivalent to conventional T-glass, and glass cloth 2 is equivalent to conventional S-glass.

[0187] • Glass cloth 1: T-glass manufactured by Nitto Boshoku Co., Ltd., type 2118 (SiO2: 66% by mass, Al2O3: 25% by mass, MgO: 7.3% by mass, and P2O5: 0% by mass).

[0188] • Glass cloth 2: S3 glass, type 2118 manufactured by Nan Ya Plastics Industrial Co., Ltd. (SiO2: 66% by mass, Al2O3: 25% by mass, MgO: 6.1% by mass, and P2O5: 0.003% by mass)

[0189] • Glass cloth 3: V-type glass manufactured by Nitto Boshoku Co., Ltd., type 2118 (SiO2: 50% by mass, Al2O3: 25% by mass, MgO: 2.3% by mass, and P2O5: 12% by mass).

[0190] [Examples 1-7 and Comparative Examples 1-3]

[0191] (Evaluation of sample preparation)

[0192] First, a resin varnish was prepared. All components except the molybdenum compound particles and inorganic filler were added to methyl ethyl ketone (MEK) according to the composition (parts by mass) listed in Table 1 and mixed to achieve a solids concentration of 40–50% by mass. The resulting mixture was stirred for 60 minutes. Then, the molybdenum compound particles and inorganic filler were added to the resulting mixture according to the composition (parts by mass) listed in Table 1 and dispersed using a bead mill. Through this process, a varnish-like resin composition (varnish) was obtained.

[0193] Next, the varnish obtained above was impregnated into the glass cloths shown in Table 1. Specifically, glass cloth 3 was used in Examples 1-7 and Comparative Example 3, glass cloth 2 was used in Comparative Example 1, and glass cloth 1 was used in Comparative Example 2. Then, the prepreg was prepared by heating and drying at 130°C for 3 minutes. At this time, the content of the component constituting the resin through the curing reaction was adjusted to be approximately 45% by mass relative to the content of the prepreg (resin content). That is, the content of glass cloth was adjusted to be 55% by mass relative to the total amount of prepreg. In addition, the curing thickness was adjusted to reach 103 μm.

[0194] Next, evaluation samples (metal foil laminates) were obtained using the obtained prepreg. First, 10 sheets of the obtained prepreg were overlapped, and copper foil (3EC-VLP manufactured by Mitsui Metals & Mining Co., Ltd.) with a thickness of 12 μm was placed on both sides. Using it as a pressing body, it was heated to a temperature of 220°C at a heating rate of 3°C / min, and heated and pressurized at 220°C for 120 minutes and a pressure of 3 MPa, thereby obtaining an evaluation substrate (metal foil laminate) with a resin layer (insulating layer) of approximately 1030 μm thick on both sides with copper foil bonded to it.

[0195] Evaluation tests were conducted using the prepregs and evaluation substrates prepared as described above, and by the methods shown below.

[0196] [Evaluation Test]

[0197] (Coefficient of thermal expansion: CTE (50~260℃))

[0198] In the evaluation test of the coefficient of thermal expansion, the bare board (cured prepreg, about 1030 μm thick) after removing the copper foil from the copper-clad laminate obtained by etching 10 overlapping prepreg sheets was used as the evaluation sample.

[0199] The evaluation sample (size: 10.0 mm × 3.5 mm) was used as a test piece, and the coefficient of thermal expansion of the evaluation substrate in the planar direction (Y direction) at a temperature below the glass transition temperature of the cured resin composition was determined by TMA (Thermo-mechanical analysis). Specifically, the measurement was performed in compression mode using a TMA apparatus (TMA / SS7100 manufactured by Seiko Electronics Nanotechnology Co., Ltd.). To eliminate the influence of thermal strain on the test piece, a 10 g load was applied to the test piece along the Y direction, and the temperature was increased from 30 °C to 320 °C at a heating rate of 10 °C / min, and then cooled to room temperature. Then, a 10 g load was applied to the test piece along the Y direction, and the temperature was increased from 30 °C to 320 °C at a heating rate of 10 °C / min. During this heating, a temperature displacement diagram was obtained. Then, based on the temperature displacement diagram obtained at this time, the average coefficient of thermal expansion in the range of 50–260 °C was calculated. The lower the average coefficient of thermal expansion (CTE), the better the result. In this test, if the average coefficient of thermal expansion (CTE) is below 6.5 ppm / °C, it is judged as "pass".

[0200] (Drill bit wear rate)

[0201] like Figure 1 As shown, two evaluation substrates (metal foil laminates) 11 were overlapped, and a cover plate 16 was placed on top of them. Using a drill bit 15 and under the following processing conditions, 10,000 holes were drilled from the cover plate 16 to the evaluation substrate (metal foil laminate) 11 on which the cover plate 16 was placed. The size (area) of the drill bit's cutting edge after drilling was measured. The wear rate of the drill bit's cutting edge was calculated based on the measured size (area) of the drill bit's cutting edge after drilling and the size (area) of the drill bit's cutting edge before drilling. In this test, if the drill bit wear rate is 30% or less, it is judged as "pass".

[0202] Cover plate: LE-G0612 0.18mm

[0203] Number of overlapping pieces: Overlap two 1.0mm pieces.

[0204] Hole: 0.15mm in diameter and 2.5mm in depth

[0205] Drill bit number: NEU-L088BW

[0206] Rotation speed: 200Krpm

[0207] Delivery speed: 12μm / rev

[0208] The results of the above evaluations are shown in Table 1.

[0209]

[0210] [Inspection]

[0211] As shown in Table 1, it was confirmed that the prepregs of Examples 1-7, which used the resin composition and glass cloth of this embodiment, exhibited low coefficients of thermal expansion and low drill wear rates. Furthermore, Examples 1-6, which used an allylbenzoxazine compound as the benzoxazine compound (C), had even lower coefficients of thermal expansion compared to Example 7, which did not use an allylbenzoxazine compound.

[0212] On the other hand, the prepregs of Comparative Examples 1-2, which did not use the glass cloth of this embodiment, showed that at least one of their coefficients of thermal expansion and drill bit wear rates was worse than those of the Examples. Furthermore, the prepreg of Comparative Example 3, which did not contain molybdenum compound particles, was damaged when the drill bit wear rate was measured.

[0213] This application is based on Japanese Patent Application No. 2024-056462, filed on March 29, 2024, the contents of which are incorporated herein by reference.

[0214] To illustrate the invention, it has been adequately and sufficiently described above with reference to the accompanying drawings and embodiments. However, it should be recognized that modifications and / or improvements to the above embodiments can be readily made by those skilled in the art. Therefore, any modified or improved embodiments implemented by those skilled in the art, as long as they do not depart from the scope of protection of the claims, are to be interpreted as being included within the scope of protection of the claims.

[0215] Industrial availability

[0216] According to the present invention, it is possible to provide a prepreg with excellent drilling machinability (low drill bit wear rate) and a low coefficient of thermal expansion, and a metal foil laminate and wiring board using the prepreg.

Claims

1. A prepreg, characterized in that... include: Thermosetting resin composition or a semi-cured product of said thermosetting resin composition; And glass cloth, among which, The thermosetting resin composition contains molybdenum compound particles (A) and maleimide compound (B). Relative to the total composition of the glass cloth, the glass cloth contains: 45-55% by mass of SiO2; 20-30% by mass of Al2O3; less than 3.0% by mass of MgO; and 10-15% by mass of P2O5.

2. The prepreg according to claim 1, characterized in that, The molybdenum compound particles (A) comprise molybdenum compound particles (A-1) that have been surface-treated with a surface treatment agent.

3. The prepreg according to claim 1, characterized in that, The cumulative 50% particle size (D) of the volume-based particle size distribution of molybdenum compound particles (A) 50 The size ranges from 0.1 μm to 2.0 μm.

4. The prepreg according to claim 1, characterized in that, The content of molybdenum compound particles (A) in the thermosetting resin composition is 0.1 to 40 parts by mass relative to 100 parts by mass of the resin component in the thermosetting resin composition.

5. The prepreg according to claim 1, characterized in that, The thermosetting resin composition also contains a benzoxazine compound (C).

6. The prepreg according to claim 5, characterized in that, Benzoxazine compounds (C) include allyl benzoxazine compounds (C-1).

7. The prepreg according to claim 5, characterized in that, The mass ratio (C / B) of the benzoxazine compound (C) to the maleimide compound (B) is 0.2 or more and 1.0 or less.

8. The prepreg according to claim 1, characterized in that, The thermosetting resin composition contains an elastomer (D) comprising at least one of a high molecular weight substance (D-1) with a weight average molecular weight of 10,000 or more and 900,000 or less, and a core-shell rubber (D-2).

9. The prepreg according to claim 8, characterized in that, The high molecular weight substance (D-1) includes at least one of an acrylic resin and a styrene copolymer.

10. The prepreg according to claim 8, characterized in that, The content of elastomer (D) in the thermosetting resin composition is 5 to 40% by mass relative to the total amount of resin components in the thermosetting resin composition.

11. The prepreg according to claim 1, characterized in that, The thermosetting resin composition also contains inorganic filler (E). The inorganic filler material (E) comprises at least one selected from the group consisting of silica particles, aluminum hydroxide particles, talc particles, magnesium hydroxide particles and boehmite particles.

12. The prepreg according to claim 1, characterized in that, The content of the thermosetting resin composition in the prepreg is 35 to 80% by mass relative to the total amount of components in the prepreg.

13. A metal foil-coated laminate, characterized in that... include: An insulating layer comprising the prepreg of any one of claims 1 to 12; as well as Metal layer.

14. A wiring board, characterized in that... include: An insulating layer comprising the prepreg of any one of claims 1 to 12; as well as wiring.

Citation Information

Patent Citations

  • Nano-lubrication method

    JP2024056462A

  • Molybdenum compound powder, prepreg, and laminate

    WO2013047203A1

  • Resin composition, prepreg and laminate

    WO2013146700A1